Differential Effect of Initiating Moderate Red Wine Consumption on 24-h Blood Pressure by Alcohol Dehydrogenase Genotypes: Randomized Trial in Type 2 Diabetes - Gepner, Yftach (Am J Hypertens, 2016)
AIMS: Observational studies report inconsistent associations between moderate alcohol intake and blood pressure (BP). In a sub-study of a larger randomized controlled trial, we assessed the effect of initiating moderate red wine consumption on 24-h BP recordings and the effect of a common genetic variant of alcohol dehydrogenases (ADH) among patients with type 2 diabetes. METHODS: Fifty-four type 2 diabetes, alcohol abstainers were randomized to consume 150ml/dinner dry red wine or mineral water. Both groups were guided to adhere to a Mediterranean diet, without caloric restriction. We measured 24-h ambulatory BP monitoring (ABPM) at baseline and after 6 months. RESULTS: Participants (age = 57 years; 85% men; mean 24-h BP = 129/77mm Hg) had 92% 6-month retention. After 6 months of intervention, the average 24-h BP did not differ between the wine and water groups. A transient decrease in BP was observed in the red wine group at midnight (3–4 hours after wine intake: systolic BP: red wine = −10.6mm Hg vs. mineral water = +2.3mm Hg; P = 0.031) and the following morning at 7–9 am (red wine: −6.2mm Hg vs. mineral water: +5.6mm Hg; P = 0.014). In a second post hoc sub-analysis among the red wine consumers, individuals who were homozygous for the gene encoding ADH1B*2 variant (Arg48His; rs1229984, TT, fast ethanol metabolizers), exhibited a reduction in mean 24-h systolic BP (−8.0mm Hg vs. +3.7mm Hg; P = 0.002) and pulse pressure (−3.8mm Hg vs. +1.2mm Hg; P = 0.032) compared to heterozygotes and those homozygous for the ADH1B*1 variant (CC, slow metabolizers). CONCLUSIONS: Initiating moderate red wine consumption at dinner among type 2 diabetes patients does not have a discernable effect on mean 24-h BP. Yet, a modest temporal BP reduction could be documented, and a more pronounced BP-lowering effect is suggested among fast ethanol metabolizers. CLINICAL TRIALS REGISTRATION: ClinicalTrials.gov Identifier: NCT00784433.